Welfare economics : - Ng, Yew-Kwang (Palgrave Macmillan, 2004)
This book attempts to make welfare economics more complete by discussing the recent inframarginal analysis of division of labor and by pushing welfare economics from the level of preference to that of happiness, making a reformulation of the foundation of public policy necessary.